Oxidative Stress and Inflammatory Mediators in Exhaled Breath Condensate of Patients with Pulmonary Tuberculosis. A Pilot Study with a Biomarker Perspective - Silvia Guzmán-Beltrán; Laura Elena Carreto-Binaghi; Claudia Carranza; Martha Torres; Yolanda Gonzalez; Marcela Muñoz-Torrico; Esmeralda Juárez (MDPI AG, 2021)
Tuberculosis (TB) is one of the highest infectious burdens worldwide. An excess of inflammation and inadequate antioxidant defense mechanisms are believed to lead to chronic inflammation and lung damage in tuberculosis (TB). However, circulating metabolites do not always replicate lung-associated biomarkers that define the pathobiology of the disease. The objective of this study was to determine the utility of exhaled breath condensate (EBC), a non-invasive and straightforward sample, to evaluate alveolar space-derived metabolites of redox state and inflammation. We assessed the levels of exhaled oxidant/antioxidant parameters (8-isoprostane, MDA, GSH), inflammatory markers, such as nucleosomes, cytokines (IL-2, IL-4, IL-6 and IL-8, IL-10, GM-CSF, TNF-α, and IFN-γ) and lipid mediators (PGE2, LTB4, RvD1, and Mar1), in patients with recently diagnosed pulmonary TB and healthy controls' EBC and serum. The TB patients showed 36% lower GSH levels, and 2-, 1.4-, 1.1-, and 50-fold higher levels of 8-isoprostanes, nucleosomes, IL-6, and LTB4, respectively, in EBC. There was no correlation between EBC and serum, highlighting the importance of measuring local biomarkers. Quantitation of local inflammatory molecules and redox states in EBC would help find biomarkers useful for pharmacological and follow-up studies in pulmonary tuberculosis.